Viabilitas Benih Jagung Lokal (Zea mays L.) Kabupaten Timor Tengah Utara Yang Diberi Perlakuan Kolkisin - Polikarpia Wilhelmina Bani; Maria Delia Fuka Seran; Emilia Julyanti Bria (BIOEDUSCIENCE, 2023)
Background: Colchicine is a chemical mutagen that has been widely used to increase the viability of a plant. Most of the people of the North Central Timor (TTU) Regency still depend on local agricultural products, so one of the crops cultivated during the rainy season is local corn. This study aimed to determine the viability of local maize seeds in North Central Timor Regency and the appropriate concentration of colchicine to increase local maize germination. Methods: used in this research is an experimental method that gives colchicine treatment to 3 local corn varieties. The colchicine used was 0% (control), 40%, and 60%. The viability parameters observed were maximum growth potential (PTM), germination capacity (DB), and vigor index (IV). Results: showed that there were variations in the measurement of viability parameters observed both at maximum growth potential (PTM JBa 16,6%, JBu 35%, JKa 10%, JKu 8,33%), germination (DB 70%, JBu 81,66%, JKa 60%, JKu 61,66%) and vigor index (IV 68,33%, JBu 78,33%, JKa 63,33%, JKu 68,33%). Conclusions: the appropriate concentrations of colchicine to increase local corn germination were 40% and 60%, respectively. This can be seen in the viability parameters that show differences, namely the maximum growth potential (PTM) of flower corn with a colchicine concentration of 40%, which is 35%, the germination capacity (DB) of flower corn with a colchicine concentration of 60%, which is 90%, and the vigor index (IV) of flower corn. The concentration of colchicine 60% is 90%.